Modern Synthesis and Chemistry of Stabilized Ketene N,O-Acetals - Paris, Timothy J.; Willand-Charnley, Rachel (Synthesis, 2022)
Ketene N,O-acetals are robust and versatile synthons. Herein, we outline the synthesis of stable ketene N,O-acetals in the twenty-first century. In addition, we review recent developments in the chemistry of ketene N,O-acetals, as it applies to the vinylogous Mukaiyama aldol reaction, electrolysis, and pericyclic transformations. While dated reports rely on in situ use, modern methods of ketene N,O-acetal synthesis are heavily oriented towards producing products with high ‘bench’ stability; moreover, in the present century, chemists typically enhance the stability of ketene N,O-acetals by positioning an electron-withdrawing group at the β-terminus or at the N-position. As propitious substrates in the vinylogous Mukaiyama aldol reaction, ketene N,O-acetals readily provide polyketide adducts with high regioselectivity. When exposed to electrolysis conditions, the title functional group forms a reactive radical cation and cleanly couples with a variety of activated olefins. Given their electron-rich nature, ketene N,O-acetals act as facile substrates in several rearrangement reactions; further, ketene N,O-acetals reserve the ability to act as either dienophiles or dienes in Diels–Alder reactions. Lastly, ketene N,O-acetals are seemingly more stable than their O,O-counterparts and more reactive than analogous N,N- or S,S-acetals; these factors, in combination, make ketene N,O-acetals advantageous substitutes for other ketene acetal homologues.1 Introduction2 Select Methods of Stabilization-Oriented Ketene N,O-Acetal Synthesis3 Ketene N,O-Acetals in the Vinylogous Mukaiyama Aldol Reaction4 Ketene N,O-Acetals in Anodic Coupling and Electrochemical Oxidation Reactions5 Rearrangement and Diels–Alder Reactions of Ketene N,O-Acetals6 Conclusions, Perspectives, and Directions
Keywords: ketene acetals; push-pull alkenes; imide enolates; vinylogous Mukaiyama aldol reaction; Kobayashi reaction; electrolysis; rearrangement; Diels–Alder reactions